Precarious and less well paid? Wage differences between permanent and fixed-term contracts across the EU - António Dias da Silva; Alessandro Turrini (Institute for the Study of Labor (IZA), 2015)
We analyse wage differences between permanent and fixed-term contracts across the EU using data from the European Structure of Earnings Survey. We find that, after controlling for individual and job characteristics, workers on permanent contracts earn on average about 15% more than workers on fixed-term contracts with similar observable characteristics. The permanent contract wage premium is higher for men, workers at middle age and with middle education, and performing non-elementary occupations. We also find that permanent workers enjoy a higher wage premium for education and age. We explore cross-country differences in the wage premium for permanent workers and correlate them with indicators of labour market institutions. In particular, results indicate that the wage premium is higher the stricter is employment protection for permanent contracts and the higher the share of temporary employment, which supports the view that workers with fixed-term contracts suffer from a negative wage gap due to lower bargaining power.
Keywords: J31; J41; J42; 330; contract type; wage premium; segmentation